PEMBENTUKAN KARAKTER KATEKIS DALAM TERANG EVANGELII GAUDIUM - Jelahu, Timotius Tote (SEPAKAT-Jurnal Pastoral Kateketik, 2016)
This article explores the development of the coaching orientation at TahasakDanum Pambelum Pastoral College, the diocese of Palangka Raya. Theexistence not only produces graduates to fill government demands, but as aplace for catholicâs regeneration in Central Kalimantan. In carrying out themessage, the Pastoral College is a home to prepare a generation characterizedby the Christian faith. Facing todayâs global challenge, the apostolic appeal ofEvangelii Gaudium may be an inspiration to develop a coaching pattern thatis in line with the vision of the College